Antioxidant Potential Of Eugeniajambolana Seed; A Randomized Clinical Trial In Type 2 diabetes Mellitus - G. SHIVAPRAKASH; M. R. S. M. PAI; M. NANDINI; K. RESHMA; D. A. SAHANA; K. RAJENDRAN; A. SHIRWAIKAR; M. R. ADHIKARI PRABHA; JYOTHI GANESH (International Journal of Pharma and Bio Sciences, 2011)
Diabetes mellitus (DM) is a growing global problem where, increased oxygen free radicals are responsible for the complications. Clinical evidence of Eugenia jambolana seeds for use in DM is lacking. This is an open labeled, randomized trial in DM patients: fifteen in group1 received Eugenia Jambolana seed powder 10 gm orally per day along with diet and exercise, and ten in group 2 on diet and exercise alone. Follow-up visits were: V0=randomization; V1-V6, after one to six months of therapy. Patients were followed up for blood sugar, glycosylated hemoglobin, fasting insulin, antioxidants from V0 to V6 in group 1 and V0 to V3 in group 2. Results revealed in group1: reduced Fasting blood sugar (FBS) fromV3-V6 [140(18), 125(26.5), 124(19.5), 134(24)]; rise in SOD (superoxide dismutase) at V3[3255(2394)] and V6[4650(3517)]; reduced HOMA-IR (homeostasis model assessment for insulin resistance) at V3 [5(6.8)] and V6 [5.5(3.3)]; negative correlation between SOD and FBS at V3(ρ= -0.5) and V6(ρ=-0.577) which were significant at (P<0.05). Study shows the antihyperglycemic and antioxidant potential of Eugenia jambolana seed powder and a negative correlation between the antioxidant and antihyperglycemic action.